Mitigating Effect of the Sea on Temperatures Along Mediterranean Coastal Areas: The Case of the Vine Territory of the Matera DOP in Basilicata (Italy) - Pasquale Cirigliano; Stanislao Esposito; Edmondo Di Giuseppe; Andrea Cresti (Atmosphere)
This study aims to assess temperature variations caused by ongoing climate change in the Basilicata region, southern Italy—Ionian side of the Gulf of Taranto—on the territory of the Matera DOP vineyard. In particular, it aims to assess the influence of the sea on temperature trends, and particularly to its “mitigating effect” in the context of ongoing climate change. Temperature trends were analyzed using ERA5-Land data from 1981 to 2022 and data from weather stations of the Lucanian Agency for Development and Innovation in Agriculture from 2000 to 2023. Temperature trends were studied considering both the period of the vegetative-productive season of the vineyards and the whole year. The results of this study show that, for the historical period analyzed, the Matera DOP area showed a significant upward trend in temperatures, particularly in the inland areas. This increase, especially for minimum temperatures, is more evident at higher elevations than at lower elevations near the sea. Indeed, coastal areas benefit from the thermoregulatory effect of the Ionian Sea, which moderates temperature increases at lower elevations. It follows that the Matera DOP wine-growing areas, and particularly those furthest from the coastal strip, will have to adapt to harsh climatic conditions that will certainly affect the quality and typicality of the wines.